4D printing with robust thermoplastic polyurethane hydrogel-elastomer trilayers. (5th February 2019) - Baker, Anna B.; Bates, Simon R.G.; Llewellyn-Jones, Thomas M.; Valori, Laurie P.B.; Dicker, Michael P.M.; Trask, Richard S.
Abstract: Here we present a new 4D printing technique capable of producing a diverse range of trilayer constructs using commercial low-cost desktop 3D printers. This unique methodology permits the viable construction of dynamically robust and complex origami architectures for a new generation of active structures. The resulting creations transform from flat 2D parts to 3D structures through submersion in water and return to their original configuration through dehydration. This technique uses commercially available materials and printers to enable a 4D printing method that is more accessible and affordable than previous examples of hydration triggered 4D printing. This method yields a controlled and predictable actuation route and final shape, enabling it to be used for both simple and complex origami inspired designs, such as the tessellated waterbomb origami pattern, a design that has not previously been realised with 4D printing. These new designs demonstrate how the integration of multiple trilayers into a single 3D print enables through-thickness control of actuation and resulting formation of active structures with complexity beyond what has previously been achieved with 4D printing. Graphical Abstract: Highlights: Thermoplastic polyurethane hydrogel filament was manufactured and 3D-printed into multi-material structures. A range of trilayer constructs with hydration-triggered hydrogel hinges were produced using low-cost desktop 3D printers. The effect of varying hinge geometry on the final actuation angle and the transient actuation progression was investigated. Complex tessellated origami structures were produced which had not been previously realised by 4D-printing.